Fluorescence spectroscopy of osthole binding to human serum albumin - Guang-De Yang; Cong Li; Ai-Guo Zeng; Yuan Zhao; Rong Yang; Xiao-Li Bian (Elsevier, 2013)
The interaction of human serum albumin (HSA) with osthole was investigated by fluorescence spectroscopy. Osthole can quench the fluorescence of HSA and the quenching mechanism is a static process. The binding site number n and apparent binding constant K were measured at different temperatures. The thermodynamic parameters ÎH0, ÎG0 and ÎS0 were calculated at different temperatures. The results indicated that electrostatic forces played a major role in the interaction of osthole with HSA. Results of osthole synchronous fluorescence and UV absorption spectra showed that the microenvironment and conformation of HSA were changed. Keywords: Osthole, Human serum albumin, Fluorescence quenching